A new chromosomal race (2n=44) of Nannospalax xanthodon from Turkey (Mammalia: Rodentia). Issue 3 (3rd July 2017) - Kankılıç, Teoman; Arslan, Atilla; Şeker, Perinçek Seçkinozan; Kankılıç, Tolga; Toyran, Kubilay; Zima, Jan
Abstract : A new karyotype for blind mole rats was recorded in Tunceli province in Eastern Turkey. The karyotype contained 44 chromosomes, including 13 biarmed pairs, 7 acrocentric pairs, and one heteromorphic pair with a submetacentric and an acrocentric homologue in the autosomal complement (FNa=69). The X chromosome was submetacentric and the Y chromosome medium-sized subtelocentric (FN=73). Distinct dark centromeric C-bands were observed on most of the biarmed and three pairs of the acrocentric autosomes. The NORs were detected on short arms of three subtelocentric pairs and one acrocentric pair of autosomes. The diploid number of chromosomes and the karyotype characteristics observed are obviously unique among hitherto studied populations of blind mole rats and the complement can be evaluated as a new chromosome race of Nannospalax xanthodon . The distribution ranges of individual chromosome races of the species recorded in Eastern Anatolia are revised and possible interracial hybridization is discussed in respect of the finding of a new race.